Vitamins in Animal and Human Nutrition. - McDowell, Lee Russell (John Wiley & Sons, 2008)
Vitamins in Animal and Human Nutrition contains concise, up-to-date information on vitamin nutrition for both animals and humans. The author defines these nutrients and describes their fascinating discovery, history and relationship to various diseases an.